Disruption or Catalyst? Foreign Banks' Impact on Competition in Indonesia's Islamic-Conventional Banking Ecosystem - Maharani, Novita Kusuma; Alwahidin, Alwahidin (Faculty of Economic and Business, 2025)
Research Originality: This study uniquely examines the impact of foreign bank penetration on bank competition within Indonesia's dual-banking system. By incorporating the moderating effect of Islamic banks, this research provides novel insights into the dynamics of bank competition in a multi-faceted financial ecosystem.Research Objectives: This study investigates the impact of foreign banks on the level of competition in Indonesia's dual-banking system, encompassing both Islamic and conventional banks.Research Methods: The study employs panel data analysis of Islamic and conventional banks in Indonesia from 2011 to 2021. Bank competition and foreign bank penetration are measured using the Lerner Index and various ratios of foreign banks, respectively.Empirical Results: The findings reveal that an increase in the number of foreign banks enhances bank competition and reduces market power. However, increased foreign bank asset ownership is associated with reduced competition. While not statistically significant, Islamic banks tend supports increased competition in the banking sector.Implications: To maintain a competitive balance, regulators should focus on controlling foreign asset ownership rather than merely the number of foreign banks. Furthermore, the role of Islamic banks in fostering competition warrants consideration in policy formulation.JEL Classification: C1, E52How to Cite:Maharani, N. K., & Alwahidin. (2025). Disruption or Catalyst? Foreign Banks’ Impact on Competition in Indonesia’s Islamic Conventional Banking Ecosystem. Etikonomi, 24(1), 1 – 16. https://doi.org/10.15408/etk.v24i1.36338.